Exploring Student’s Engagement in Learning Vocabulary Through Animation Videos - Sri Rahayu; Yousef Bani Ahmad; Acep Bahrum Kamil (Universitas Muhammadiyah Enrekang, 2021)
The purpose of this study was to see how students were involved in vocabulary learning using animated videos. This type of research is qualitative research. The participants in this study were eighth grade students at MTs Al Hasan Karawang. The research sample was 3 students who were selected based on the recommendation of the English teacher, from the most active to intermediate students in learning English. Data were collected through two instruments, namely through interviews and documentation. In the documentation, students are invited to watch learning materials using animated videos with a duration of about 5 minutes. Then after that, students were given questions to write down the new vocabulary they got from the animated video of about 10-15 words. In the interview, the researcher used semi-structured interview as the research design. Students were given several questions related to three aspects of student involvement, namely cognitive, behavioral, and emotional aspects. The research data is in the form of transcripts of short speaking recordings and answers related to interviews that have been carried out. From this study it was found that vocabulary learning using animated videos can help students in learning vocabulary (cognitive), showing positive reactions to learning (emotional), and actively participating in classroom learning (behavior).